Initiation and Regulation of Complement during Hemolytic Transfusion Reactions - Sean R. Stowell; Anne M. Winkler; Cheryl L. Maier; C. Maridith Arthur; Nicole H. Smith; Kathryn R. Girard-Pierce; Richard D. Cummings; James C. Zimring; Jeanne E. Hendrickson (Clinical and Developmental Immunology)
Hemolytic transfusion reactions represent one of the most common causes of transfusion-related mortality. Although many factors influence hemolytic transfusion reactions, complement activation represents one of the most common features associated with fatality. In this paper we will focus on the role of complement in initiating and regulating hemolytic transfusion reactions and will discuss potential strategies aimed at mitigating or favorably modulating complement during incompatible red blood cell transfusions.